Carbon stock assessment of a reforestation site within Mt. Arayat protected landscape, Pampanga, Philippines - Ojeda, Michelle N.; Jang, Minkyoung; Park, Dongkyun; Kang, Hoduck (Forest science and technology, 2024)
The Philippines has very few studies in terms of biomass production and carbon stocks in reforestation sites and the level of emission that has been avoided due to forest protection activities. Most of carbon stock estimates being used in the country are based on secondary data or studies in other countries using the same species. The study aimed to provide a reliable assessment on the contribution of reforestation sites in biomass production and carbon stocks and the potential of these plantation to contribute to the climate change mitigation efforts in the Philippines. The guideline prepared by the Philippines' Department of Environment and Natural Resources - Forest Management Bureau (DENR-FMB) in 2021 on Forest Resources Assessment (FRA) which follows the manual of Food and Agriculture Organization of the United Nations (FAO) Forestry Department in conducting FRA was used during data collection. A tract was established in the southern portion of the reforestation site wherein the species planted in 2012 are already very prominent and their diameter at breast height (DBH) and total height were measured and their corresponding wood specific gravity were taken into account. Carbon stocks were estimated using Chave et al.'s and Brown's allometric equations. The estimated carbon stocks using Chave et al.'s formula is 542.3 tC/ha while the estimated carbon stock using Brown's formula is 2001.6 tC/ha. The results of computation using Brown's equation are considerably higher than the results using Chave et al.'s equation considering that Brown's equation only took into consideration the DBH of trees while Chave et al.'s equation included the height and wood specific gravity of each species. The study demonstrated how important our forests in terms of their roles as carbon sinks and therefore contribute to our country's efforts in climate change mitigation.